High Performance Work System and Organisational Culture on Organisational Performance: A Case Study at Prodia Clinical Laboratory throughout Sumatra - Tri Annisa Irsan; Eka Fauzihardani (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to examine the influence of High Performance Work System (HPWS) and Organizational Culture on organizational performance in Prodia Clinical Laboratory in the Sumatra region. The study sample consisted of 191 employees representing various positions in the laboratory, with data collected using a 5-point Likert scale-based questionnaire. Data analysis was conducted using multiple linear regression to test the relationship between HPWS, Organizational Culture, and organizational performance. The results showed that HPWS had a positive and significant effect on organizational performance with a relatively small contribution (regression coefficient 0.113; p = 0.027). Meanwhile, Organizational Culture had a very large and significant effect (regression coefficient 1.291; p 0.001) on organizational performance. This finding confirms that the implementation of HPWS can improve organizational performance if integrated with a strong organizational culture. A conducive and productive organizational culture plays a dominant role in improving the effectiveness of performance in Prodia Clinical Laboratory. This study recommends strengthening organizational culture and consistency in implementing HPWS as the main strategy in improving laboratory organizational performance. The results of this study are consistent with previous studies that emphasize the importance of synergy between work systems and organizational culture to achieve optimal performance.